The universal semilattice compactification of a semigroup - H. R. Ebrahimi Vishki; M. A. Pourabdollah (International Journal of Mathematics and Mathematical Sciences)
The universal abelian, band, and semilattice compactifications of a semitopological semigroup are characterized in terms of three function algebras. Some relationships among these function algebras and some well-known ones, from the universal compactification point of view, are also discussed.